Islamisasi Ilmu Al-Attas: Framework dan Implementasi - Baharuddin AbdRahman (DIRASAT: Jurnal Studi Islam dan Peradaban, 2019)
This research is exposing al-Attas’ program of Islamization of Knowledge, focusing on the frame work of the Islamization of knowledge and its implementation in the education curriculum. Using the library research method, this research succeeded in compiling a number of Islamic frame works and steps for their implementation. Among the work frames are: (1) identifying, (2) isolating, (3) formulating, (4) integrating, and (5) spreading. Identifying is finding secular elements and traditions that are not of Islamic value in the body of knowledge, and then isolating them by freeing the body of knowledge from secular elements and un-Islamic values found embedded in the body of knowledge. Being formulating is the activity of compiling key concepts and Islamic values. The formulation is then integrated into the core knowledge which will be deployed in the Islamic education curriculum.